2010
DOI: 10.1007/s00330-010-1809-4
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance-guided upper abdominal biopsies in a high-field wide-bore 3-T MRI system: feasibility, handling, and needle artefacts

Abstract: Biopsies of the upper abdomen can be performed with great technical success and easy handling because of the large-bore diameter. The MRI-guided biopsy needle had an acceptable susceptibility artefact at 3 T. However future research must aim to reduce the susceptibility effects of the biopsy systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 35 publications
1
21
1
Order By: Relevance
“…In this study, the average duration was 134.1 min in liver biopsies, whereas soft-tissue biopsies lasted 73.0 min on 3 min using a 3T-system [17]. The time for the MR-guided biopsies also exceeded the procedure time of comparable CT-guided biopsies [21].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In this study, the average duration was 134.1 min in liver biopsies, whereas soft-tissue biopsies lasted 73.0 min on 3 min using a 3T-system [17]. The time for the MR-guided biopsies also exceeded the procedure time of comparable CT-guided biopsies [21].…”
Section: Discussionmentioning
confidence: 96%
“…However, major disadvantages of magnetic resonance imaging (MRI) as a guiding technique are the high costs for a specialised interventional MRI-system or MRI-compatible biopsy-systems and the expected high time consumption accompanied with a loss of valuable MRI suite occupation time. Several publications have addressed the value of MRI-guided biopsy in liver and musculoskeletal lesions and in some publications the total duration of the interventions were stated [16,17]. Attempts to reduce the intervention time in using MR-fluoroscopic guidance [18] have been reported, however only one publication has focused on factors that affect the duration of MR-guided breast biopsies [19].…”
Section: Introductionmentioning
confidence: 97%
“…Stattaus et al [22] reported a sensitivity of 95.5%, specificity of 100%, and an accuracy of 96% using a short, wide-bore 1.5 T MR system. Kühn et al [23] reported an accuracy of 94%. Both groups agree that MR-guided procedures are also feasible for lesions with quite a steep angulation due to MRI’s capacity for multiplanar viewing.…”
Section: Discussionmentioning
confidence: 99%
“…The simplest way to perform interventions on a cylindrical MRI scanner is the single-step procedure as used in CT-guided interventions. To determine the location of a lesion and to monitor needle position, the patient must be moved into the isocenter of the MRI scanner and then moved back out of the scanner for incremental advancement of the needle using the freehand technique [2,6]. The interventions specified above require needles for aspiration, injection and biopsy that are visible on MRI, laser applicators, RF electrodes, and microwave antennas for ablation that are available from multiple manufacturers.…”
Section: Instruments and Operating Concepts For Oncologymentioning
confidence: 99%